If a, b, c are integers and b ≠ 0 then, a × (b - c) = a × b - a × c
Solution:
The given terms are, if a, b, c are integers and b ≠ 0 then, a × (b - c) = a × b - a × c. To prove whether the given statement is true or false let us consider some integer values for a, b and c.
Consider a = 1, b = 2 and c = 3. On substituting the values of a, b, and c in the expression a × (b - c) = a × b - a × c we have
1 × (2 - 3) = 1 × 2 - 1 × 3
-1 = -1
Therefore, after using integer rules and simplifying the expression we observed that the statement ‘if a, b, c are integers and b ≠ 0 then, a × (b - c) = a × b - a × c’ is true.
✦ Try This: State whether the statement is true or false. 4 × (5 - 6) = 4 × 5 - 4 × 6.
We can apply integer rules and the order of operations to identify whether 4 × (5 - 6) = 4 × 5 - 4 × 6 is true or false
☛ Also Check: NCERT Solutions for Class 7 Maths Chapter 1
NCERT Exemplar Class 7 Maths Chapter 1 Exercise Problem 97
If a, b, c are integers and b ≠ 0 then, a × (b - c) = a × b - a × c
Summary:
After applying the integer rules along with considering an illustration we examined that if a, b, c are integers and b ≠ 0 then, a × (b - c) = a × b - a × c is a true statement
☛ Related Questions:
visual curriculum